Estimation of acute toxicity of a drug based on the complex of lithium citrate, polymethylsiloxane, aluminum oxide - M. A. Korolev; L. N. Rachkovskaya; P. G. Madonov; A. V. Shurlyginа; E. E. Rachkovsky; A. Yu. Letyagin; V. I. Konenkov; A. A. Churin; T. Yu. Dubskaya; T. V. Vetoshkina; L. A. Sandrikina; T. I. Fomina; et al. (Сибирский научный медицинский журнал, 2020)
Research Institute of Clinical and Experimental Lymphology has developed an innovative drug based on a complex of lithium citrate, polymethylsiloxane and aluminum oxide (LOAP). Lithium-based drugs are effective in treating bipolar disorders. However, the toxic effects of lithium cause a “narrow therapeutic window”, which limits its clinical use. The creation of the drug LOAP was aimed at creating a prolonged form with a slow release of lithium to reduce toxic properties and use lithium citrate as an active pharmacological agent. At the moment, the lithium complex has no analogues. The purpose of the study was to study the parameters of acute toxicity of the LOAP. Material and methods. When studying acute toxicity, drugs were administered once intragastrically to mice and rats at doses of 12000, 10000, and 5000 mg/kg. Results. A single administration of drugs intragastrically through a probe in the maximum possible doses to mice and rats did not cause the death of animals and did not cause a locally irritating effect on the gastric mucosa. LOAP can be assigned to hazard class 4 (GOST 12.1.007-76).